Study of the Functional Outcome of Total Knee Arthroplasty in Kathmandu Medical College - Sharma, Sashmit; Rijal, Kiran Prashad; Prasai, Tanup; Poudel, A (Nepal Orthopaedic Association Journal, 2021)
Background: Total knee arthroplasty is a surgery done for correction of the biomechanics of the knee joint by altering the articular surface which is damaged in degenerative diseases like osteoarthritis. The aim of this study is to study the functional outcome of total knee arthroplasty in Nepalese patients.Method: A prospective observational study was carried out in 20 patients undergoing primary total knee arthroplasty in Kathmandu Medical College Teaching Hospital from September 2017 to September 2019. The status of the knee was assessed prior to the operation and 6 months following the surgery by using Knee Clinical Score (KCS) and the score was graded as excellent, good, fair and poor.Result: The average knee clinical score in the patients increased from 26.10 ± 5.89 to 76.30 ± 5.18 at 6 months following the surgery. The average knee functional score was 30.25 ± 6.97 prior to the surgery which increased to 77.25 ± 6.17 after the surgery. All the patients were graded to have poor knee functional and clinical grades prior to the operation. After the surgery 50% patients had excellent, 40% patients had good and 10% patients had fair Knee clinical grade while 60% patients had excellent, 35% patients had good functional outcome and 5% had fair Knee functional grade.Conclusion: Total Knee Arthroplasty is a reliable surgical option for patients with severe osteoarthritis and this surgery can provide good to excellent functional outcome in most of the patients.